2014
DOI: 10.1016/j.etp.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of azoxymethane-induced colon tumor metastasis to lung in a mouse model relevant to human sporadic colorectal cancer and evaluation of grape seed extract efficacy

Abstract: The second leading cause of cancer-related deaths (both genders combined) in the United States is colorectal cancer (CRC). This emphasizes the need to develop both effective therapies for CRC patients and pre-clinical models mimicking human disease that carry translational potential in drug-development. Notably, at present there are no in situ models of CRC metastasis to lung. In our azoxymethane-induced colon tumorigenesis study in A/J mice assessing grape seed extract (GSE) efficacy, during necropsy we also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…In addition, cytokeratin 20 was expressed severely in colonic tissues of AOM induced colon cancer. This was in accordance with Derry et al, (2014) who showed that cytokeratin 20 is considered as an additional colon biomarker and expressed virtually in epithelial cells in all cases of colorectal carcinomas. The present study revealed that C. tiglium nano-extract minimized severity of the inflammatory responses that is considered as criteria of malignancy and stage of colon cancer in nano-extract simult-treated group while these inflammatory responses were prevented completely in the post-treated group.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, cytokeratin 20 was expressed severely in colonic tissues of AOM induced colon cancer. This was in accordance with Derry et al, (2014) who showed that cytokeratin 20 is considered as an additional colon biomarker and expressed virtually in epithelial cells in all cases of colorectal carcinomas. The present study revealed that C. tiglium nano-extract minimized severity of the inflammatory responses that is considered as criteria of malignancy and stage of colon cancer in nano-extract simult-treated group while these inflammatory responses were prevented completely in the post-treated group.…”
Section: Discussionsupporting
confidence: 92%
“…AOM induces rodent colon carcinogenesis when administered over 6–8 weeks via subcutaneous or intraperitoneal injection, with a latency period ranging from 20 to 30 weeks [ 13 ]. The distribution of tumors developed in the small intestine and colon (predominantly in the distal colon) is similar to that observed in the human colon [ 21 , 40 ]. Histological and histochemical properties of AOM-induced tumors are similar to those described in humans, being classified as adenomas and adenocarcinomas.…”
Section: Rodents As Models Of Colorectal Cancersupporting
confidence: 64%
“…Due to the abundance of bioactive compounds in grape pomace seeds, particularly phenolic compounds, which comprise 5% to 8% of their weight, there has been widespread interest in exploring their potential applications [1]. These phenolics, including phenolic acids, flavonoids, and proanthocyanidins, possess various health-promoting properties such as antioxidant, antiinflammatory, and anticancer activities [2][3][4][5][6][7]. However, like many other plant matrices, grape pomace seeds contain a significant proportion of phenolic compounds existing in Foods 2024, 13, 1158 2 of 13 an insoluble form, especially after the maceration process of winemaking [8], which limits their further application based on the active phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%